CELL AND TISSUE CULTURES OF HIGHER PLANTS: A PROMISING SOURCE OF VALUABLE CHEMICAL COMPOUNDS - Urazaliyev , К.R. (Eurasian Journal of Applied Biotechnology, 2016)
A major feature distinguishing plants from bacteria and animals is the variety of synthetic processes in plants, which result in a broad range and variety of compounds, many of which are biologically active. Thus far, more than 30 000 such compounds have been identified across various chemical classes, and every year this number is increasing. In recent years, plant cell and tissue culture has advanced to the extent that sufficient plant matter can be produced and economically important secondary compounds can be produced in amounts greatly exceeding that of their naturally occurring content in plants. The way in which these valuable chemical compounds are obtained, including plant cell and tissue culture methods, significantly impact the economic viability of the production of such compounds. To develop an economical production method, different techniques were compared: the use of immobilised cells and enzymes, semi-continuous and continuous systems, higher plant cells for biotransformation, and two-stage cultivation methods, and increased growth rates of the cultured cells and yields of secondary compounds from cultured tissue and cells. This comparative study was conducted by applying a variety of techniques, including chemical and physical mutagenesis, cloning of individual lines, the use of differentiated cultures, and optimisation of growth conditions, where the primary aim was to develop cheaper technologies for the production of secondary compounds from cultured cells and tissues of higher plants.